Padronização do teste dot blotting e comparação entre testes de diagnóstico de brucelose em bovinos - Bastos, Carla Resende [UNESP] (2015)
This study aimed to standardize and evaluate the dot blotting technique for the serologic diagnosis of bovine brucellosis, compare the results with those found in the Bengal test (AAT), 2-mercaptoethanol (2-ME) and complement fixation (CF) and also estimate the relative sensitivity and specificity of dot blotting in comparison with the official diagnostic tests. In order to do this, 50 samples of bovine blood serum were used for test standardization, and two antigens were evaluated: Brucella abortus B19 bacteria obtained from ANABORTINA® B19 vaccine - Merial, after the rupture process of the microorganism, and a polysaccharide extract obtained from a sample of Brucella abortus S99 by the hot water method - hot phenol. At the end of standardization, the use of nitrocellulose membrane in a circle format was established as ideal for the technique, the antigen obtained from B. abortus bacteria after going through the rupture process of the microorganism, as a support a cell culture plate with 24 flat bottom wells was used, a dilution serum of 1:100 and the conjugate of 1:30,000, and washing 3 times per step. The evaluation and comparison of relative sensitivity and specificity with the AAT, 2-ME and CF tests was done using 1,315 samples, and these results were compared using the Kappa indicator. The comparison between the results of dot blotting and the AAT showed a Kappa index of 0.9081 (IC95%: 0.8542 - 0.9621), sensitivity of 88% (IC95%: 83.75% - 92.25%) and specificity of 99.45% (IC95%: 98.8% - 99.75%); 2-ME test, Kappa index of 0.9939 (IC95%: 0.939 - 1.0484), sensitivity of 99.48% (IC95%: 97.11% - 99.91%) and specificity of 99.91% (IC95%: 99.49% - 99.989%); complement fixation test, Kappa index of 0.8226 (IC95%: 0.7690 - 0.8761), sensitivity of 100% (IC95%: 97.42% - 100%) and specificity of 95.40% (IC95%: 94.03% - 96.47%). Using the combination of the results of 2-ME and RFC to establish the true condition of the animal, the ...